PERSEPSI PENGGUNA JASA BUS TRANS KOETARADJA TERHADAP KUALITAS PELAYANAN ANGKUTAN UMUM DI BANDA ACEH - Miftahul Husna; Daska Azis; M. Hafizul Furqan (Jurnal Samudra Geografi, 2023)
The Trans Koetaradja bus is a bus rapid transit (BRT) type of public transport, which has been operating in the city of Banda Aceh since 2016. The existence of the Trans Koetaradja Bus in Banda Aceh aims to facilitate community mobilisation in Banda Aceh and its surroundings by measuring the elements of public transport service quality which include: safety, comfort, convenience, reliability, price comparison and efficiency as well as observations using indicators of urban transport services, which include: travel time, walking distance to the shelter, number of changes, bus travel time, bus travel speed and travel cost. Research Objectives 1) To determine the perception of Trans Koetaradja bus service users on the quality of public transport services in Banda Aceh; 2) To find out the quality of Trans Koetaradja bus service in accordance with urban transport service standards. The method used in this research is a quantitative descriptive method. The study population were service users from the six corridors of Trans Koetaradja route in Banda Aceh, a total of 50 respondents. Data collection techniques in research using questionnaires and observation sheets with data processing techniques using statistical formulas. Based on the results of research and data processing by looking at the responses, most respondents stated that they strongly agreed 48% (24 people), agreed 42% (21 people), disagreed 8% (4 people) and strongly disagreed 2% (1 person) and based on the observation results stated that the Trans Koetaradja bus met the public transport service standards, although there were two criteria that were still not optimal, namely the waiting time criteria and the bus speed criteria. Both criteria are still inefficient because the Trans Koetaradja bus travel time was delayed due to the lack of a dedicated lane.